Efficacy of inhaled budesonide for the treatment of severe equine asthma. (25th September 2018) - Lavoie, J. P.; Leclere, M.; Rodrigues, N.; Lemos, K. R.; Bourzac, C.; Lefebvre‐Lavoie, J.; Beauchamp, G.; Albrecht, B.
Summary: Background: Corticosteroids are the most potent drugs for the control of severe equine asthma, but adverse effects limit their chronic systemic administration. Inhaled medications allow for drug delivery directly into the airways, reducing the harmful effects of these drugs. Objectives: To evaluate the efficacy of inhaled budesonide specifically formulated for the equine use and administered by a novel inhalation device in horses with severe asthma. Study design: Experimental studies in horses with naturally occurring asthma with cross‐over, randomised, blinded experimental designs. Methods: In Study 1, budesonide (1800 μg twice daily) administered using a novel Respimat ® based inhaler was compared to i.v. dexamethasone (0.04 mg/kg). In Study 2, 3 doses of budesonide (450, 900, and 1800 μg) were compared to oral dexamethasone (0.066 mg/kg). Lung function, bronchoalveolar fluid cytology (Study 1), CBC, serum chemistry, and serum cortisol and adrenocorticotropic hormone (ACTH) values were evaluated. Results: In Study 1, there was a marked and significant improvement in the lung function of all horses treated with budesonide and dexamethasone. Neutrophil percentages in bronchoalveolar fluid decreased in all horses treated with dexamethasone and in four of six horses treated with budesonide. Serum cortisol and blood ACTH concentrations decreased with both treatments. In Study 2, there was a significant improvement in the lung function with all dosages of budesonide, and the effects of higher dosages were comparable to those of dexamethasone. Dexamethasone and budesonide at the two higher dosages induced a significant decrease of cortisol concentrations. Main limitations: The Respimat ® based inhaler is not currently commercially available. Conclusions: Administration of budesonide with the Respimat ® based inhaler provided dose‐dependent relief of airway obstruction in horses with severe asthma, but also a suppression of serum cortisol.